Direct synthesis of secondary amines from alcohols and ammonia catalyzed by a ruthenium pincer complex - Balaraman, Ekambaram; Srimani, Dipankar; Diskin-Posner, Yael; Milstein, David (Catalysis Letters, 2015)
Efficient and selective direct synthesis of secondary amines from primary alcohols and ammonia with liberation of water has been achieved, with high turnover numbers and with no generation of waste. In case of benzylic alcohols, imines rather than amines are obtained. This atom economical, environmentally benign reaction is homogenously catalyzed by a well-defined bipyridine based Ru(II)-PNN pincer complex.
Keywords: Alcohol; Ammonia; Homogenous catalysis; Ru-pincer complex; Secondary amine